2015
DOI: 10.1024/0300-9831/a000220
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Deficiency in Patients with Acute Myocardial Infarction: An Italian Single-Center Study

Abstract: We observed very high prevalence of vitamin D deficiency among subjects with myocardial infarction in all seasons of enrollment. However, it was lower in the summer when sun exposure is higher. The exposure to sunlight may be a cost-saving therapeutic strategy for the management of vitamin D deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 0 publications
3
39
2
Order By: Relevance
“…Both the evidence of the summer shift in the temperate climate zone and, in the absence of temperate seasons, the annual correlation of this shift with the sunshine duration at the equator, are important findings that can be of relevance for understanding the etiopathogenesis of STEMI onset. The prevalence of vitamin D deficiency in patients with acute myocardial infarction has been recently discovered, and its synthesis can affect many factors that participate in the etiogenesis of atherothrombotic coronary occlusion 29, 30. However, although in our epidemiological study we show that the summer shift correlates with the levels of vitamin D, this result should be taken with some caution.…”
Section: Discussioncontrasting
confidence: 69%
“…Both the evidence of the summer shift in the temperate climate zone and, in the absence of temperate seasons, the annual correlation of this shift with the sunshine duration at the equator, are important findings that can be of relevance for understanding the etiopathogenesis of STEMI onset. The prevalence of vitamin D deficiency in patients with acute myocardial infarction has been recently discovered, and its synthesis can affect many factors that participate in the etiogenesis of atherothrombotic coronary occlusion 29, 30. However, although in our epidemiological study we show that the summer shift correlates with the levels of vitamin D, this result should be taken with some caution.…”
Section: Discussioncontrasting
confidence: 69%
“…Low levels of vitamin D have been associated with increased risk of CVD such as coronary artery disease (CAD) [5], myocardial infarction (MI) [67], hypertrophy [8], cardiomyopathy [9–10], fibrosis [1112], heart failure (HF) [1314]. In addition, deficiency of vitamin D has been found in arterial diseases, including aneurysm [1516], peripheral arterial disease (PAD) [1719], arterial calcification [20], hypertension (HTN) [2122] and atherosclerosis [23] (Figures 2 and 3).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to single reports suggesting that higher vitamin D levels confer mortality benefits, [39][40][41]43,47,66,67 a number of randomized controlled trial meta-analyses demonstrate the consistency of the inverse relationship between vitamin D level and mortality from any cause.…”
Section: Increased Risk Of All-cause Mortalitymentioning
confidence: 99%
“…Several important associations exist between VDD and acute myocardial infarction (AMI): VDD is highly prevalent in AMI [37][38][39][40][41][42][43] ; risk of AMI is significantly higher and inversely proportional to the degree of VDD 37 ; and AMI patients with VDD fare significantly worse with greater morbidity, postinfarction complications, and higher mortality. [39][40][41]43 One study found rates of major cardiovascular events were 50% higher with vitamin D insufficiency and 80% higher with VDD.…”
Section: Greater Incidence Morbidity and Mortality For Acute Myocardmentioning
confidence: 99%
See 1 more Smart Citation